How can the analysis of reserve dynamics after fire support the phenological insight of Bulbostylis paradoxa (Spreng.) Lindm (Cyperaceae)? - Rosalem, Patrícia Fernanda [UNESP]; Martins, Aline Redondo [UNESP]; Camargos, Liliane Santos [UNESP] (Elsevier, 2022)
Carbohydrate reserves are an essential key to plant survival from disturbance. Therefore, studying the different storage organs and types of reserves makes it possible to understand the dynamics of singular plants such as Bulbostylis paradoxa (Spreng.) Lindm, which presents flowering triggered by fire in the Cerrado. Physiological response to fire frequency is detailed by measuring the plant's reserves after a fire disturbance and which carbohydrates are more available for its use. It was measured the concentrations of starch, amino acids, total soluble carbohydrates and soluble proteins in leaves (control), flowers (burning) and caudex of B. paradoxa, in unburned individuals (control), and burned individuals (annually and biennially, obtained 48 h and 15 days after fire). Starch concentrations increased at both fire frequencies in all parts of the plant, as did carbohydrate concentrations. In amino acids, an increase in the concentration of flowers from individuals burned biennially 48 h after fire was observed. The protein concentration showed a decrease in burned plants. Furthermore, the two burning frequencies and the days following the fire can influence the storage of such reserves.
Keywords: Amino acids; Bulbostylis paradoxa; Carbohydrates; Cerrado; Fire; Flowering; Starch